Maternal Dietary Forsythia suspensa Extract Supplementation Induces Changes in Offspring Antioxidant Status, Inflammatory Responses, Intestinal Development, and Microbial Community of Sows - Long, Shenfei; Wang, Qianqian; He, Tengfei; Ma, Jiayu; Wang, Jian; Liu, Sujie; Wang, Hongliang; Liu, Li; Piao, Xiangshu (Frontiers in Veterinary Science, 2022)
This experiment aims to investigate the effect of maternal diet supplemented with Forsythia suspensa extract (FSE) on the performance, antioxidant status, inflammatory responses, intestinal development, and microbial community of sows. 24 gestating sows (Landrace × Yorkshire) were assigned to 2 treatments with 12 sows per treatment. From d 107 of gestation to d 21 of lactation, sows were supplemented with a basal diet as control (CON), or a FSE diet (basal diet + 100 mg/kg FSE). Compared with CON, sows fed FSE showed lower (P < 0.05) wean-to-estrus interval, body weight loss, and higher (P < 0.05) average daily gain of suckling piglet. Sows fed FSE had reduced (P < 0.05) serum malondialdehyde (MDA) content and enhanced (P < 0.05) catalase and glutathione peroxidase (GSH-Px) contents at farrowing and weaning compared with CON. The suckling piglets of FSE-fed sows had increased (P < 0.05) mRNA expressions of nuclear factor erythroid-2 related factor 2, heme oxygenase-1 in liver, and lower (P < 0.05) serum MDA content on d 0, 7 and 14 of lactation. Sows fed FSE had lower (P < 0.05) serum tumor necrosis factor-α (TNF-α) and interleukin-8 (IL-8) contents at farrowing, and reduced (P < 0.05) serum IL-6 and IL-8 contents at weaning compared with CON. Piglets from FSE-fed sows had enhanced (P ≤ 0.05) villus height and villus height to crypt depth ratio in jejunum, and higher (P < 0.05) protein expression of Occludin in jejunal mucosa compared with CON. Sows fed FSE tended to have higher (P = 0.09) relative abundance of Lactobacillus at genus level in feces at weaning, while their offspring had higher (P < 0.05) relative abundance of Lactobacillus at genus level in colon and cecum at weaning compared with CON. Our results showed maternal diet supplemented with FSE in lactating sows could effectively induce improvement of performance, antioxidant status, anti-inflammatory function, intestinal morphology, barrier function and microbial community in their offspring.